Early Infectious Diseases Specialty Intervention Is Associated With Shorter Hospital Stays and Lower Readmission Rates: A Retrospective Cohort Study. (13th June 2018) - Schmitt, Steven; MacIntyre, Ann T; Bleasdale, Susan C; Ritter, J Trees; Nelson, Sandra B; Berbari, Elie F; Burdette, Steven D; Hewlett, Angela; Miles, Matthew; Robinson, Philip A; Siddiqui, Javeed; Trotman, Robin; et al.
Abstract : Among inpatients less than 65 years diagnosed with infection, involvement of an infectious disease (ID) specialist was associated with lower mortality, shorter length of stay, and lower cost. ID involvement by day 3 was associated with better outcomes than later involvement. Abstract: Background: Intervention by infectious diseases (ID) physicians improves outcomes for inpatients in Medicare, but patients with other insurance types could fare differently. We assessed whether ID involvement leads to better outcomes among privately insured patients under age 65 years hospitalized with common infections. Methods: We performed a retrospective analysis of administrative claims data from community hospital and postdischarge ambulatory care. Patients were privately insured individuals less than 65 years old with an acute-care stay in 2014 for selected infections, classed as having early (by day 3) or late (after day 3) ID intervention, or none. Key outcomes were mortality, cost, length of the index stay, readmission rate, mortality, and total cost of care over the first 30 days after discharge. Results: Patients managed with early ID involvement had shorter length of stay, lower spending, and lower mortality in the index stay than those patients managed without ID involvement. Relative to late, early ID involvement was associated with shorter length of stay and lower cost. Individuals with early ID intervention during hospitalization had fewer readmissions and lower healthcare payments after discharge. Relative to late, those with early ID intervention experienced lower readmission, lower spending, and lower mortality. Conclusions: Among privately insured patients less than 65 years old, treated in a hospital, early intervention with an ID physician was associated with lower mortality rate and shorter length of stay. Patients who received early ID intervention during their hospital stay were less likely to be readmitted after discharge and had lower total healthcare spending.